Enhancing the structural integrity of earthen blocks by gaur-xanthan synergy : A Review - Asif Afzal Naik; Er Preetpal Singh (Bulletin of Engineering Science, Technology and Industry, 2025)
Earth blocks have long been a preferred construction material in rural regions worldwide. There is a growing awareness and need to develop sustainable and environmentally sound alternatives to traditional building materials. The review on enhancing the structural integrity of earthen blocks using the synergy of guar gum and xanthan gum forces on how these biopolymers can improve the mechanical properties of traditional earthen materials.Studies have shown that the optimal concentration of these gums can lead to a notable increase in the durability and longevity of earthen structures, making them more suitable for various environmental conditions. The combination not only contributes to the mechanical properties but also enhances the workability of the earthen mix, allowing for easier construction processes.These amendments aim to improve the soil’s workability, strength, and resistance to environmental factors. The paper explores a variety of innovative structural systems that have been proposed in recent years and highlights different systems. Each system represents a unique solution to the challenges of traditional masonry, offering improved structural stability and ease of construction of earthen blocks.This innovation is essential for locations with a high demand for earth block masonry systems, notably earthquake active areas. Given the critical requirement for safe and resilient construction in such areas, the paper investigates the seismic performance of interlocking masonry systems, emphasizing the importance of seismic experiments in determining the safety and reliability of these systems.